Soviet Economic Development Since 1917 - Dobb, Maurice, 1900-1976 (London Routledge & Kegan Paul Ltd, 1953)
Fine copy in the original stiff-card wrappers. Particularly and surprisingly well-preserved; tight, bright, clean and especially sharp-cornered. Slight pencil scoring to text. ; 8vo 8" - 9" tall; 515 pages; Description: vii, 515 p. : maps (on end papers) ; 22 cm. Subjects: Soviet Union -- Economic conditions -- 1917-1955.
Include Maps and Index
Keywords: Soviet Union -- Economic conditions -- 1917-1945 -- Economic History